2020
DOI: 10.1002/hon.2730
|View full text |Cite
|
Sign up to set email alerts
|

Good prognosis for follicular lymphoma with estrogen receptor α‐positive follicular dendritic cells

Abstract: Follicular lymphoma (FL) has a meshwork of follicular dendritic cells (FDCs). We previously demonstrated the presence of estrogen receptor alpha (ERα) + CD23 + FDCs in grades 1-2 FL. The significance of FDCs as a prognostic factor in FL remains unknown. The current study aimed to compare clinicopathological features, including prognosis, between FL with and without ERα + FDCs. This study evaluated the clinicopathological significance of ERα expression in 70 FL patients by immunostaining. The presence of ERα mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In FL, FDC phenotype recapitulates that observed in GC dark zone FDC, with positivity for CD21 and Clusterin, but weak or negative expression of CD23, CD35 and ICAM1 5 , 27 , 32 . Recently, the expression of estrogen receptor in FDC in cases FL was found to be associated with low grade and good prognosis 41 , while positivity of CD14 was an independent predictor of transformation into large B cell lymphoma 29 .…”
Section: Fdc In Hematological Disordersmentioning
confidence: 99%
“…In FL, FDC phenotype recapitulates that observed in GC dark zone FDC, with positivity for CD21 and Clusterin, but weak or negative expression of CD23, CD35 and ICAM1 5 , 27 , 32 . Recently, the expression of estrogen receptor in FDC in cases FL was found to be associated with low grade and good prognosis 41 , while positivity of CD14 was an independent predictor of transformation into large B cell lymphoma 29 .…”
Section: Fdc In Hematological Disordersmentioning
confidence: 99%
“…Similarly, another group reported that Grade 3 FL exhibited a significant decrease of CD23 expression by the FDCs as compared with G1 FL, although CD21 expression was not significantly different [40]. Furthermore, Ohe et al reported that high estrogen receptor α expression on FDCs was an independent prognostic factor for OS and PFS in FL patients [41].…”
Section: Follicular Dendritic Cell Role In Healthy and Neoplastic Folliclesmentioning
confidence: 92%